Assessing the Role of Recreational Activities in Physical Education Participation of College Students in One State University in Laguna Philippines - John Michael D. Aquino (International Journal of Multidisciplinary Sciences, 2023)
Physical education (PE) is a crucial component of a well-rounded education because it equips the holistic aspects of the students required to live a healthy and active lifestyle. The objective of this study is to assess the role of recreational activities on physical education participation. This study explores the students’ profile, role of recreational activities in physical education participation and its relationship among 2nd year college students in one state university in Laguna, Philippines. This research employs descriptive design and random sampling method in determining the respondents. The researcher analyzed the gathered data from the administered validated self-made questionnaire. The results showed that the respondents relished the recreational activities immensely and actively participated which demonstrate that the recreational activities enabled physical activity, intellectual and emotional stimulation, and interaction with others.  The high levels of participation illustrates that the students enjoyed the games and that they benefited to their overall enjoyment of physical education courses. Consequently, the results emphasize the respondents' favorable feelings toward physical education classes along with their strong drive to get involved and prosper in their classes. Their desire to learn and pursue new physical activities is indicative of their proactive approach to PE. The significance of nurturing a supportive and active physical education environment that encourages the holistic development and well-being of students is highlighted. It is recommended to utilize the designed process handbook to prioritize the incorporation of recreational activities into their curricula and provide an atmosphere of encouragement to have an active engagement and enjoyment.